(untitled) (Al-Aasar, 2025)
Allah sent Prophets for the guidance of the Human beings, among them Prophet Muhammadﷺ was the last. In the short span of time approximately twenty three years, He ﷺ changed the scenario of the world through Islamic teachings. The life of Prophet Muhammad ﷺ is superb example for human beings. There are countless of Muslims and non- Muslim scholars wrote about His ﷺ life. From the beginning the Seerah of Prophet Muhammad ﷺ remained an interesting topic for th researchers. The Seerah of Prophet Muhammad us primarily through the Qur’an, the hadith literature, and the sīrah literature (biographies written by Muslim historians), which provide accounts of his life and teachings. Islamic scholars and historians described and discussed the life of Prophetﷺ while using different approaches and styles. We have a number of Seerah books such as Arabic, Persian, English, Urdu, Pashto etc. In which the life of the prophet Muhammad ﷺ has been described comprehensively. This study investigate the style and research methodology of the selected Urdu Seerah books رحمۃ اللعٰلمین ،سیرت النبی ﷺ اور سیرۃ المصطفیٰ ﷺ.